Corrigendum to "A novel experimental methodology to identify fracture envelopes and cohesive laws in mixed-mode I+III" [Eng. Fract. Mech. 214 (2019), 304–319]. (15th March 2022) - Loh, Lukas; Marzi, Stephan
Abstract: The original manuscript (Loh and Marzi, 2019) [1] deals with experimental investigations on mixed-mode fracture in adhesively bonded joints. It presents a novel test setup and proposes two different methods to evaluate the experimental data. Unfortunately, the description of the novel test evaluation methods contains fundamental errors that are corrected in this Corrigendum. After taking the necessary corrections into account, the indirect evaluation method no longer appears suitable for determining traction vectors, as it was proposed in the original manuscript.